A gestão orientada para processos e os impactos dos construtos cultura organizacional, estrutura organizacional e gestão de pessoas no desempenho organizacional - Nathália de Melo Santos (2012)
This study aimed to describe the nature of the association between theconstructs organizational structure, organizational culture and human resource W management, considering the assumptions of the BPO, and identify the relationship r between them and the construct organizational performance, considering the four critical areas of the BSC: iinancial, customer/market, processes/skills and learning/growth. To achieve this goal, were treated secondary data extracted from ai sample of 368 brazilian companies of medium and large size industry and serviceS organizations - located in different states. Hypotheses were tested for association and effects between the constructs of the nomothetic research model, having been employed in the tests, univariate and multivariate statistics, Through the testing ofthe nomothetic model proposed and structural equation modeling, it was possible to identify theexistence of positive and statistically significant associations between the constructs investigated, except for the relationship between organizational structure and , organizational performance. These results extend the study area and allow newr interpretations of the theme, besides providing for the establishment of new research ideas that seek to generalize and to corroborate the findings presented here.